2020
DOI: 10.1080/13639080.2020.1767765
|View full text |Cite
|
Sign up to set email alerts
|

Community-based intervention and marginalised youth: inclusion, social mobility and life-course transition

Abstract: The University of Gloucestershire accepts no liability for any infringement of intellectual property rights in any material deposited but will remove such material from public view pending investigation in the event of an allegation of any such infringement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 42 publications
0
23
0
1
Order By: Relevance
“…For students that have experienced alienation in school, these relationships can have a greater impact compared to their peers (Muller, 2001 cited in Crosnoe et al, 2004) [13] with some studies showing a direct link between the quality of relations and school retention and the prevention of early school leaving [14][15][16][17][18][19]. These relationships can not only influence student attendance and retention, but also a student's sense of belonging in school [17,[20][21][22] Where early school leavers are re-engaging with education in alternative settings, 'trust, recognition and acceptance' appear to be key elements in positive staff-learner relationships that can lead to (re)engagement in education and 'more positive and productive life choices' for young people (p. 6) [20].…”
Section: Introductionmentioning
confidence: 99%
“…For students that have experienced alienation in school, these relationships can have a greater impact compared to their peers (Muller, 2001 cited in Crosnoe et al, 2004) [13] with some studies showing a direct link between the quality of relations and school retention and the prevention of early school leaving [14][15][16][17][18][19]. These relationships can not only influence student attendance and retention, but also a student's sense of belonging in school [17,[20][21][22] Where early school leavers are re-engaging with education in alternative settings, 'trust, recognition and acceptance' appear to be key elements in positive staff-learner relationships that can lead to (re)engagement in education and 'more positive and productive life choices' for young people (p. 6) [20].…”
Section: Introductionmentioning
confidence: 99%
“…One study used a combination of feedback sheets, focus groups and interviews (Hickey, 2018). Four studies combined observations, interviews and focus groups Flores, 2016;Morgan, 2020;Thompson, 2022). Two studies used interviews, observations and journaling (Gowland-Pryde, 2016;Nicklin, 2017), and one study each employed a mix of interviews and journaling (Ruggiero, 2013), reading, journaling and discussion groups (Seroczynski, 2011).…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…It is only by acknowledging the reality of these in uences, the mechanisms by which they are sustained, and the effects on vulnerable populations, that interventions can be focused to promote desirable outcomes. Morgan et al (2020) also reported that certain context-speci c conditions associated with community-based interventions should be made public to promote the possibility of these initiatives adding value to the understanding of social integration and inclusion. The government-led interventions which were focused on the restoration of mangrove swamps and oil spill clean-up reported little to no success due to ineffective monitoring processes, bureaucratic practices and corrupt practices (Zabbey & Tanee, 2016;Eni & Okpiliya, 2011).…”
Section: Policy Measures Available For Mitigating the Incidence Oil S...mentioning
confidence: 99%